Efficacy and Safety of Simultaneous Application of HIFEM and Synchronized Radiofrequency for Abdominal Fat Reduction and Muscle Toning: A Multicenter Magnetic Resonance Imaging Evaluation Study. Issue 7 (July 2021) - Jacob, Carolyn; Kent, David; Ibrahim, Omer
Abstract : BACKGROUND: Radiofrequency and high-Intensity Focused Electromagnetic (HIFEM) field procedure are well-known, stand-alone, body-shaping modalities, yet their simultaneous application has not been investigated. OBJECTIVE: The aim is to evaluate the efficacy of a novel device simultaneously delivering HIFEM and radiofrequency for subcutaneous fat reduction and muscle toning. MATERIALS AND METHODS: Forty-one subjects with an average age of 39.7 ± 11.5 years were recruited. The subjects received 3 abdominal treatments (one per week). Magnetic resonance imaging images of the treated area were evaluated at baseline and at 1-, 3-, and 6-month visits for changes in subcutaneous fat, muscle thickness, and abdominal separation (AS). Anthropometric data and digital photographs were collected. Subject satisfaction and therapy comfort were evaluated. RESULTS: The muscle mass increase peaked at 3 months, showing 26.1% thickening. The fat thickness reduction was most prominent at 3 months, showing a 30.8% reduction. The AS decreased by 18.8% at 3 months after treatment. The waist circumference reduced by 5.87 ± 3.64 cm at a 3-month follow-up. Six-month data showed maintenance of these outcomes. The treatment was considered as comfortable with high patient satisfaction. CONCLUSION: The analysis of magnetic resonance imaging images and waist measurements showed that the therapy combining HIFEM and radiofrequency is highly effective in reducing subcutaneous fat and muscle thickening.